A comprehensive optimization and design analysis of a heat exchanger with coiled wire turbulators - Kapan, Sinan; Celik, Nevin; Turgut, Emre; Tanyildizi, Vedat (Springer, 2023)
The turbulator inserted in a heat exchanger is one of the most important methods of enhancing heat transfer passively. It is known that especially coil wire turbulators increase turbulence intensity and thus heat transfer as a vortex generator. Experimental analysis is required to see how the independent parameters, such as thickness, pitch, length and the flow regime affect the increasing heat transfer with increasing pressure loss. For this purpose, in this study, optimum conditions are investigated by using three well-known experimental analysis methods; (i) optimum parameter levels are determined by Taguchi Experimental Design Method (DoE), (ii) Analysis of Variance method (ANOVA) is used in order to determine the effects of each design parameters on the result, and finally (iii) Grey Relational Analysis is applied to the results of heat transfer and pressure drop to obtain the relationship between the highest heat transfer and the lowest pressure drop. The three pitch ratios (p/d = 0.2, 0.3 and 0.4), three thickness ratios (e/d = 0.033, 0.066 and 0.1), three length ratios (l/d = 5, 10 and 15) of coil wire turbulator and six values of Reynolds number ranging from 30 000 to 80 000 are considered to be the design parameters of the experimental study. The extracted results are plotted by means of Nusselt number (Nu), friction factor (f) and thermal performance factor (TPF) which includes both Nusselt number and friction factor in one formula. The experimental outcome showed that the optimum Nusselt number is achieved under the conditions of Re = 80 000, e/d = 0.1, p/d = 0.4 and l/d = 15. On the other hand, the optimum value for the friction factor is obtained under the conditions of Re = 70 000, e/d = 0.033, p/d = 0.4 and l/d = 5. According to Grey Relational Analysis, the design parameters allowing for multi-performance (highest Nu with lowest f) are; Re = 80 000, e/d = 0.1 p/d = 0.3 and l/d = 5.
Keywords: Grey Relational Analysis; Solar Air Heater; Zno Buffer Layer; Taguchi Approach; Corrugated Tube; Circular Tube; Performance; Parameters; Inserts; Flow